PENANGANGAN KAWASAN KUMUH DI BEBERAPA DAERAH DI JAWA DAN SUMATERA - Weldy Anugra Riawan (Karimun University, 2022)
The role of local governments in the sustainable development agenda has not yet fully achieved the 11th SDGS goal, which is to make cities and human settlements inclusive, safe, resilient, and sustainable. This study aims to formulate an out of the box strategy in responding to the 11 SDGS goals so that it can be achieved by Regional Governments in Indonesia using qualitative descriptive analysis methods based on primary and secondary data. The results of the study indicate that local government programs that must be encouraged in order to succeed in this goal are to facilitate sustainable natural resource management in slum and coastal settlements by protecting and improving ecosystems, encouraging disaster risk reduction/management, overcoming slums, thoroughly, community, institutional, collaboration, based on strategy formulation. Recommendations based on research results are: encourage programs that are characterized by